CFD-DEM combined the fictitious domain method with monte carlo method for studying particle sediment in fluid. (17th November 2018) - Ma, Shengli; Wei, Zhengying; Chen, Xueli
ABSTRACT: The interaction between a particle and the viscous fluid and then the particle-wall collision in the flow field plays an important role in the study of particulate flow. In this paper, we examine the velocity characteristics of a spheroidal particle sediment in the fluid and its rebound dynamics by applying the Computational Fluid Dynamics-Discrete Element Method (CFD-DEM). The Fictitious Domain method and Monte Carlo method are combined to improve the accuracy of the hydrodynamic force acting on the particle. A soft-sphere scheme of DEM is used to model the collision of particles, and the hydrodynamic force on the particle is fully solved directly from the CFD-DEM. The numerical results are verified by comparing the previous numerical and experimental results. The results are in good agreement with the corresponding published data. The simulation results show that the critical factor that affects the particle rebound is Stokes number (St). No rebound occurs when Stokes number is equal to 3.74. Initially, the results show that the ellipsoid particle shows large "wiggles" down the square tube at 45° angle with respect to the horizontal axis. These large "wiggles" gradually reduce after a time, and the ellipsoid finally settles into a stable horizontal state in the center of the square tube due to the effect of fluid viscosity dissipation.